Are functional regions more homogeneous than administrative regions? A test using hierarchical linear models - Alexandra Wicht; Per Kropp; Barbara Schwengler (Papers in Regional Science, 2019)
We investigate whether economic functional regions capture spatial clustering of core economic indicators better than administrative regions. For this purpose, we use hierarchical linear models to measure the degree of homogenization of different regional delineations. Our results for Germany show that economic functional regions tend to capture spatial clustering better than administrative ones. However, a considerable amount of clustering at a lower aggregation level cannot be accounted for by economic functional regions, especially around metropolitan centres. Furthermore, economic functional regions, which depict commuting interrelations well, are less able to capture spatial homogenization than other economic functional delineations.
Keywords: 300; functional regions; Germany; modularity; regional labour markets; spatial correlation